1996
DOI: 10.1017/s0033291700034723
|View full text |Cite
|
Sign up to set email alerts
|

Treatment, expressed emotion and relapse in recent onset schizophrenic disorders

Abstract: SynopsisThe effect of in-patient and individual orientated psychosocial intervention (IPI) and in-patient and individual and family orientated intervention (IPFI) across levels of expressed emotion (EE) on relapse was compared in a group of patients with recent onset schizophrenic disorders. Patients were randomly assigned to an individual orientated psychosocial intervention programme or to an identical psychosocial programme plus a behavioural family intervention. Seventy-six patients were studied during a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(143 citation statements)
references
References 16 publications
2
139
0
2
Order By: Relevance
“…Number needed to treat not reported as inappropriate to the outcomes. Linszen et al 1996). Family interventions showed a consistent and significant benefit, with a number needed to treat of eight, and an absolute difference in risk of relapsing of 12n8%.…”
Section: Relapsementioning
confidence: 91%
“…Number needed to treat not reported as inappropriate to the outcomes. Linszen et al 1996). Family interventions showed a consistent and significant benefit, with a number needed to treat of eight, and an absolute difference in risk of relapsing of 12n8%.…”
Section: Relapsementioning
confidence: 91%
“…The fourth study (Xiong et al, 1994) did not find significant differences in relapse rates, although patients who received family treatment were hospitalized less over the 18-month follow-up period than patients who received routine treatment. An additional study by Linszen et al (1996), not included in Table 6, compared the effects of standard treatment plus behavioral family therapy (Falloon et al, 1984) with those of standard treatment plus intensive individual therapy. Nine-month cumulative relapse rates were quite low for both groups (16% and 15%, respectively), indicating the equivalence of behavioral family treatment to individual treatment.…”
Section: Efficacy Statusmentioning
confidence: 99%
“…Ideally, if the patient can be led to note that the danger of the psychosis outbreak lies in the fact that the patient feels himself to be completely mentally healthy. Linszen et al 36 have suggested that single-family intervention usually provides individualized psychological support for family members in terms of: (i) information on the mental illness, (ii) patient management and coping with the illness and its symptoms, (iii) how to identify and solve the specific health problems and (iv) the needs of an individual family accurately. Studies have reported that contacts and interactions between group participants may affect their emotional support and practical help, which is extended to the post-intervention period 37 .…”
Section: Introductionmentioning
confidence: 99%